2000
DOI: 10.3171/jns.2000.92.1.0100
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemorrhage and edema following brain biopsy in rats: significance of mean arterial blood pressure

Abstract: The brains of SHR rats with elevated systemic MABPs are probably protected against excessive hemorrhage during surgery because of greater resistance in the larger cerebral arteries and, thus, reduced cerebral intravascular pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…It is possible that acute changes in blood pressure (rather than prolonged hypertension) may be more important in haematoma expansion. Benveniste et al 59 examined ICH after a brain biopsy and found no difference in haemorrhage volume between SHR and WKY rats, but found increased haemorrhage in normotensive WKY rats subjected to acute increases in blood pressure.…”
Section: Mechanisms Of Brain Injury/therapeutic Approachesmentioning
confidence: 99%
“…It is possible that acute changes in blood pressure (rather than prolonged hypertension) may be more important in haematoma expansion. Benveniste et al 59 examined ICH after a brain biopsy and found no difference in haemorrhage volume between SHR and WKY rats, but found increased haemorrhage in normotensive WKY rats subjected to acute increases in blood pressure.…”
Section: Mechanisms Of Brain Injury/therapeutic Approachesmentioning
confidence: 99%
“…A rat study found acute BP elevation in either normotensive or hypertensive rats after ICH, which is associated with higher HE, more brain swelling, and worse neurological deficits (154, 155). Since acute ICH leads to activation of the adrenergic system, the role of antiadrenergic agents needs to be explored.…”
Section: Hematoma Expansionmentioning
confidence: 99%
“…However, in one study we observed the opposite pattern; that is, systemic cooling provided greater protection as intervention delay increased from 1 to 12 hours after collagenase infusion (MacLellan et al, 2004). In that study, early cooling exacerbated bleeding, which likely occurred because cooling increased blood pressure, which itself worsens bleeding (Benveniste et al, 2000), and cooling may have also slowed clotting. As our focal cooling method does not notably affect blood pressure or body temperature Auriat et al, 2012), we had hoped that this method would be a safer alternative to systemic cooling.…”
Section: Discussionmentioning
confidence: 61%